Artificial intelligence planning techniques for adaptive virtual course construction (2011)
This paper aims at presenting a planning model for adapting the behavior of virtual courses based on artificial intelligence techniques, in particular using not only a multi-agent system approach, but also artificial intelligence planning methods. The design and implementation of the system by means of a pedagogical multi-agent approach and the definition of a framework to specify the adaptation strategy allow us to incorporate several pedagogical and technological approaches that are in accordance with the teamwork points of view, thus providing a very concrete implementation and installation. A novel pre-planner was included that allows transparency and neutrality within the proposed model and which also offers support to translate the virtual course elements within a planning problem specification.The final section exhibits the experimental platform SICAD+ (Sistema Inteligente de Cursos ADaptativos+, meaning "Intelligent Systemfor Adaptive Courses through a Multi-Agent System approach"), which validates the model proposed.